Income Sources and Resource Use in Crop Production on Different Land Forms in the Upper Luni Basin - Sehara, D B.S; Mrithyunjaya, Mrithyunjaya; Purohit, M L (Annals of Arid Zone, 2016)
Income sources and resource use in crop production were studied in different land form units of Raipur Guhia catchment of Upper Luni basin in western Rajasthan. Crop production was the principal source of household income followed by animal husbandry and subsidiary sources. Fertilizers were more critical than either mechanical or labour inputs. Increased use of manures and fertilizers are suggested for increasing the crop production in various land form units.